On Job Training Vocational Education: Producing Addiction Counsellors in Drug Addiction Social Rehabilitation Centre - Fajar Utama Ritonga; Agus Suriadi (Tunas Harapan Ummat Foundation, 2025)
Many service programs in organizational settings implement aftercare programs, but few talk about social rehabilitation aftercare programs for drug addicts. The purpose of this study was to provide care for ex-drug users who were not yet ready to return to their families or the home environment in which the ex-drug user was familiar and took drugs for the first time. It is well known that aftercare programs for ex-drug users are still very broad and that utilization of drug social rehabilitation clinics is uncommon. The Social Rehabilitation Center for Victims of Substance Abuse (BRSKP NAPZA INSYAF MEDAN) was the location of the study. North Sumatra Province, Indonesia. Using a qualitative descriptive research approach, informants consisted of 6 individuals who used comprehensive interviewing methods for gathering data techniques. The results Aftercare programme, which was initially formed by accident, has positive results in preventing relapse and is able to produce counsellors who can work to help others in the social rehabilitation process. Until now, the aftercare programme has not been required to be part of the social rehabilitation programme at Insyaf Medan Social Rehabilitation Centre. The author hopes that this programme can be continued and become a mandatory programme for all drug social rehabilitation institutions in Indonesia, whether government-owned, private or non-governmental organisations.